Preference degree of jam made with rocoto chilli (Capsicum pubescens) and pineapple (Ananas comosus) - Contreras, Eliana G. (2015)
The pace of life of the current population has led to changes in eating habits and people are likely to suffer from gastric problems. The rocoto chilli is palatable, contains vitamins, antioxidants, and has been reported that consumption of chilies benefits the digestive system. This research aimed to evaluate acceptance and consumer preference to the processed food from the binary combination of a natural fruit pulp and rocoto chilli ; two differents jams formulations to pineapple pulp and rocoto chilli pulp (ratios 1:4 and 1:8) were developed, being used sugar, pectin , potassium sorbate and citric acid, rocoto chilli pulp and pineapple pulp. The preference degree of potential consumer (53 judges aged 17 to 50 years old) was evaluated, significant differences were detected between the two jams formulations (α=0,01), 02 formulation being preferred; 62,26% of consumers expressed a willingness to purchase the preferred jam. The attributes sensory evaluated: color, smell, consistency and flavor, semi-trained panel (16 judges) was used, significant differences were detected in the intensity of color (α<0,05), the other attributes: smell, taste and consistency, judges did not detect difference between the two formulations (α=0,05). The 01 formulation pH 3.45; 75°Brix and 5700 cp at 60 rpm; the 02 formulation showed pH 3,35; 66°Brix and 4500 cp at 60 rpm.